Wideband acoustic microscopy of tissue. - Daft, C; Briggs, G (1989)
A scanning acoustic microscope (SAM) has been used to measure the elastic properties of tissue with a resolution of around 8 mum. This is achieved by broadband excitation of the acoustic lens, and the recording of an undemodulated returning signal. A method of analyzing this information to yield sound velocity, acoustic impedance, section thickness, and acoustic attenuation is described. Results from a sample of skin tissue are presented and compared with data from a computer simulation of the experiment.